Ceará e a tendência de uma matriz energética com geração predominantemente eólio-elétrica - Santos, Nicorray de Queiroz (2015)
Given the current scenery in Brazil, the replacement of the traditional hydrothermal-based power generation model for a hydro/wind-based one is very promising. It is worth to mention that the Brazilian power system has been based on hydropower generation for decades, but the energy matrix was gradually supplemented by the addition of thermal sources derived from fossil fuels. Recently, renewable energy sources such as biomass, solar, and wind have also been included. Within this context, the participation of the wind power has become significant since 2005, while the state of Ceará has shown great potential for the exploitation of such energy resource. In order to support the integration of the wind power to Ceará energy matrix, the profiles of capacity factors are evaluated in this work aiming at energy planning regarding wind farms. Considering the wind farms currently in operation, it can be stated that the hourly average wind speed for the analyzed period is 8.54 m/s for the database among the years 2012 and 2014. The Rayleigh and Weibull distribution functions also allow comparing the capacity factors obtained in simulation tests and actual data for the period between 2009 and 2014, involving 35 wind farms, defined according to the ONS grid procedures. Besides, it is possible to effectively compare the actual capacity factors with the predicted ones. The average capacity factor, which has been determined empirically in operating plants, is 39.9%, while the value corresponding to the distribution function curves, the FCavg, is 48%. Thus, the replacement of the current hydrothermal generation model for a hydro-wind-power-based one, in some regions of Brazil, is viable and of great importance within the current scenery of water reserves. The study also reveals that wind farms now account for 23.7% of the load demand in the state of Ceará, which is currently equal to 2 GWp. It is then possible to increase its contribution to 40%, thus increasing the installed capacity by 12.3%. In other words, it implies increasing the installed power from 1.1 GW to 2 GW, while the average capacity factor of 475 MWavg per year is increased to 800 MWavg, with the consequent diversification of Ceará energy matrix. This difference is estimated at 325 MWavg, which corresponds to more than 30 wind farms rated at 30 MW each